PENGARUH DIET NASI DARI PADI (Oryza sativa L.) KULTIVAR CEMPO IRENG, CEMPO ABANG, DAN IR-64 TERHADAP STRUKTUR HISTOLOGIS HATI DAN GINJAL TIKUS PUTIH (Rattus norvegicus Berkenhout, 1769) HIPERLIPIDEMIA - , NITA NURRAHMAWATI, Ardaning Nuriliani, S.Si., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Hyperlipidemia can increased risk for certain chronic health condition, such as liver disease, and chronic kidney disease. Hyperlipidemia can be prevented by antioxidants which contained in pigmented rice such as Cempo Ireng (black rice) and Cempo Abang (brown rice). Therefore this research was aimed to determine the effect of rice (Oryza sativa L.) cultivars Cempo Ireng, Cempo Abang, and IR-64 on the histological structure of hyperlipidemic albino ratâs liver and kidney (Rattus norvegicus Berkenhout, 1769). The research was carried out on 25 male albino rats. The rats were divided into 5 groups: control group, hyperlipidemic control, dietary treatment with white rice, brown rice, and black rice. Rats were given daily oral administration at the dose of 2 mL/200 g BW mixture solution of 1% cholesterol, pork oil, and duck egg yolks in the ratio 1:1, for 30 days. At the second stage hyperlipidemic condition were maintained, the rats in treatment groups were fed with pellets containing 30% rice from the cultivars IR-64, Cempo Abang, and Cempo Ireng for 30 days. At the third stage hyperlipidemic induction were stopped, while the dietary treatment with white rice, brown rice, and black rice were maintened for15 days. After 75 days of treatment, the rats were sacrified. The liver and kidneys were sampled. Histological preparations were made by paraffin method, fixed in10% formalin solution, sliced with 6 Î¼m thickness, and stained with Haematoxylin- Eosin. Supporting data include ratio of organ weight and rat weight. Ratio of organ weight and rat were analyzed using one way ANOVA. Measurement of organ weight ratio did not show any indication of kidney or liver enlargement. The result of this research showed that the dietary treatment with brown and black rice were able to decreased parenkimatosa degeneration, hidrophic degeneration, lipid degeneration, necrosis, and protein cast on albino ratâs liver and kidney. Ratio of organ weight and rat weight indicate no significant difference (p>0,05) between control and treatment groups. Therefore it could be concluded that the dietary treatment with brown and black rice can improve histological structure of hyperlipidemic albino ratâs liver and kidney.